Rage - Woodward, Bob 1943- (Simon & Schuster, 2020)
An essential account of the Trump presidency draws on interviews with firsthand sources, meeting notes, diaries, and confidential documents to provide details about Trump's moves as he faced a global pandemic, economic disaster, and racial unrest